The Contribution of Curable Plasmid-Mediated Resistance in Isolates of Staphylococcus aureus at the University of Benin Teaching Hospital, Benin City, Nigeria - Onemu, S. O; Ademulegun , Faith; Onemu-Metitiri, M. O.; Obeagu, Emmanuel Ifeanyi; Hassan, Abdulwasiu Oladele (Asian Journal of Dental and Health Sciences, 2023)
aureus, is an important human pathogen and commensal that is responsible for infections ranging from minor to deep-seated life-threatening conditions. Multi-drug resistant S. aureus or MRSA is a major cause of hospital acquired infection (HAIs) or nosocomial infections with consequential reduction in treatment options and overtly increased cost of healthcare, morbidity and mortality. The study was conceived to determine the contribution of curable transmissible plasmids to the ever-increasing proportion of multi-drug resistant S. aureus at the University of Benin Teaching Hospital, Benin City. A total of 448 consecutive multi-drug resistant clinical isolates of S. aureus were collected, confirmed by SCT and TCT and resistance to commonly used antimicrobial agents. Each isolate was inoculated into Mueller-Hinton Broth containing 100 µg/mL acridine orange and incubated at 37oC for 24 h. Each broth culture was subsequently sub-cultured onto blood agar plates and incubated at 37oC for 24 h. Sensitivity tests were thereafter done on each sub-culture by the Kirby-Bauer disc diffusion method. SCT and TCT were re-tested on each sub-culture. Isolates with curable transmissible plasmids were 31/448(6.9%) and there was complete reversion to sensitivity in all the cured strains to antimicrobial agents tested including ampicillin. The remaining isolates (93.1%) retained their resistance to all the antimicrobial agents. The isolates with curable plasmids (6.9%) also lost the coagulase activity of both types. Plasmid-mediated resistance in S. aureus remain an important route of multi-drug resistance, however this is dwarfed by chromosomally-mediated resistance as the major mechanism of resistance in multi-drug resistance S. aureus. Additionally, the cure of drug resistance was also concomitantly associated with lose of the pathogenicity factor-coagulase in these isolates. Keywords: S. aureus, multi-drug resistance, transmissible plasmids.